BROADBAND PARABOLIC ANTENNA WITH SPIRAL RADIATOR FOR UAV COMMUNICATION SYSTEM - Gritsev, Yaroslav; Shcherbyna, Olga (Science-based technologies, 2026)
The modern development of unmanned aerial vehicles (UAVs) requires stable communication channel over long distances. The main challenge in UAV control is maintaining high throughput and eliminating interference during aircraft maneuvers. Using parabolic antenna in combination with helical feed is one of the most effective solutions for ground control stations, as this design combines high gain with the advantages of circular polarization. The system is based on parabolic reflector, which serves as a focusing element. A paraboloid was chosen for its ability to form narrow beam pattern, which is critical for increasing range. However, the key innovation in this configuration is the use of the helical antenna as the parabolic reflector's feed. Unlike linear polarization, circular polarization prevents signal fading when the UAV maneuvers. The helical antenna eliminates the need for precise alignment of the polarization planes of the transmitter and receiver antennas. Helical structures also have the ability to operate over wide frequency range without significantly changing impedance. Circularly polarized antennas effectively reject signals reflected from the ground or buildings, since the polarization rotation direction reverses upon reflection, preventing it from being received by the main antenna. The paper calculates the dimensions of the parabolic dish and the helical feed to achieve optimal gain/sidelobe ratio. Simulation and experimental design studies demonstrate that the developed antenna has operating frequency range of over 1 GHz with a VSWR < 1.5 (operating frequency range from 5.7 to 6.7 GHz). Simulation results for the parabolic antenna with helical feed demonstrated the half-power beamwidth (HPBW) of 12.3 degrees for the lower frequency of the operating range and 9.6 degrees for the upper frequency, which meets the requirements for the ground segment of the UAV control system. Sidelobe levels do not exceed –15 dB across the entire operating frequency range. The antenna gain, obtained through simulation, averages 23.5 dBi across the operating frequency range. The axial ratio remains consistently below 2 dB across the entire operating frequency range of 5.7–6.7 GHz. This antenna system is ideal for tactical systems where communication reliability is a priority.